Investigation of polycystic ovarian syndrome: variation in practice and impact on the speed of diagnosis. Issue 2 (23rd February 2021) - Karia, Amar M.; Duff, Christopher J.; Heald, Adrian H.; Britton, Ingrid; Fryer, Anthony A.; Wu, Pensée
Abstract : Objective: Accurate diagnosis of polycystic ovarian syndrome (PCOS) enables clinical interventions/cardiometabolic risk factor management. Diagnosis can take over 2 years and multiple clinician contacts. We examined patterns of PCOS-associated biochemical investigations following initial consultation prior to pelvic ultrasound scan (USS). Methods: We determined in 206 women (i) the range of different biochemical test panels used in the diagnosis of PCOS in primary/secondary care prior to USS relative to national guidance in the UK and (ii) the relation between testing patterns and time to USS to highlight potential delays introduced by inappropriate testing. Results: In these 206 women, 47 different test combinations were requested at initial venepuncture; only 7 (3%) had the test panel suggested in UK guidance (follicle-stimulating hormone/luteinizing hormone/testosterone/sex hormone-binding globulin/prolactin). The number of tests performed prior to USS varied from one test to all seven tests. There was an inverse relation between the number of biochemistry tests requested at initial venepuncture episode and 'time to scan'. Those who had <3 tests had a significantly longer time from first request to USS (median 70 days) than those with 3–7 tests (median 40 days; P  = 0.002). One venepuncture episode prior to USS was associated with shorter 'time to scan' (median 29 days) than those with 2–4 episodes (median 255 days; P  < 0.001). Conclusion: There was no identifiable pattern to biochemical investigations requested as part of the initial diagnostic evaluation in women with suspected PCOS. We recommend standardization of the initial biochemical panel of analytes for PCOS workup, with incorporation into hospital/general practice ordering software systems.